Activity sensing using WIFI CSI - Zhang, Li Wen (Nanyang Technological University, 2024)
Behavior recognition plays a crucial role in various fields such as environmental monitoring, smart healthcare, intelligent furniture, and human-computer interaction, and has been a focal point in academia. Presently, research on WiFi-based human behavior recognition technology represents a novel direction in this domain. In comparison to traditional methods like sensor-based, image-based, or UWB recognition, WiFi-based approaches overcome drawbacks such as the need for wearables, sensitivity to light, and high recognition costs. Moreover, they exhibit high perceptual sensitivity and recognition accuracy, making them suitable for indoor behavior recognition. Consequently, they promise to revolutionize control methodologies for smart furniture.